2012
DOI: 10.1128/iai.05896-11
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction between Candida albicans and Commensal Oral Streptococci in a Novel In Vitro Mucosal Model

Abstract: Candida albicans is a commensal colonizer of the gastrointestinal tract of humans, where it coexists with highly diverse bacterial communities. It is not clear whether this interaction limits or promotes the potential of C. albicans to become an opportunistic pathogen. Here we investigate the interaction between C. albicans and three species of streptococci from the viridans group, which are ubiquitous and abundant oral commensal bacteria. The ability of C. albicans to form biofilms with Streptococcus oralis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
241
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(262 citation statements)
references
References 63 publications
16
241
2
3
Order By: Relevance
“…Cavalcanti et al, 2016 reported that biofilm growth and hyphal filament production by C. albicans is enhanced by S. oralis and there was growth synergy between oral bacteria Actinomyces oris and C. albicans, and between S. oralis and C. albicans, resulting in augmentation of total biofilm biomass in each case. Since S. oralis facilitates invasion of oral mucosal epithelium by C. albicans (Diaz et al, 2012), concurrently S. oralis growth is enhanced by the fungus. In addition, the pathogenic properties and invasive potential of streptococci bacteria could be augmented by C. albicans (Falsetta et al, 2014 andXu et al, 2014).Our results revealed that the highest mortality rate occurred in Nile tilapia fish in the S. iniae+ C. albicans infected group (76.19%) which was maximum during the 1 st week post infection (38.10%), followed by those infected with S. iniae alone (61.9%) and then the C. albicans infected group (57.14%).…”
Section: Discussionmentioning
confidence: 99%
“…Cavalcanti et al, 2016 reported that biofilm growth and hyphal filament production by C. albicans is enhanced by S. oralis and there was growth synergy between oral bacteria Actinomyces oris and C. albicans, and between S. oralis and C. albicans, resulting in augmentation of total biofilm biomass in each case. Since S. oralis facilitates invasion of oral mucosal epithelium by C. albicans (Diaz et al, 2012), concurrently S. oralis growth is enhanced by the fungus. In addition, the pathogenic properties and invasive potential of streptococci bacteria could be augmented by C. albicans (Falsetta et al, 2014 andXu et al, 2014).Our results revealed that the highest mortality rate occurred in Nile tilapia fish in the S. iniae+ C. albicans infected group (76.19%) which was maximum during the 1 st week post infection (38.10%), followed by those infected with S. iniae alone (61.9%) and then the C. albicans infected group (57.14%).…”
Section: Discussionmentioning
confidence: 99%
“…The S. gordonii cell wall-associated polypeptide SspB3 interacts directly with the C. albicans hyphae-specific agglutinin-like sequence 3 . A synergistic partnership between S. oralis, S. sanguinis and C. albicans was observed, where the fungus promoted biofilm formation by the streptococci on abiotic surfaces and on mucosa (Diaz et al, 2012). Thus not only S. mutans, but also C. albicans might have crucial roles for the cariogenic biofilm succession (Metwalli et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…This is likely influenced by the diverse microbiota in this environment, which we have recently described (22). Indeed, there is increasing evidence that Candida and bacteria form polymicrobial biofilms, and that some bacterial species common to the oral cavity can enhance the pathogenicity of C. albicans (35)(36)(37)(38), and that the presence of specific oral bacteria is enough to transform a C. albicans LBF into a HBF (39). We have also reported a significant association between lactobacilli and yeasts in this context, and this may be more important than C. albicans alone, as is the perceived paradigm for this DS.…”
Section: Discussionmentioning
confidence: 81%